Relationship of Postpartum Mother's Knowledge about Perineal Care with Belief in Healing Perineal Sutures in Lima Puluh Village, Lima Puluh Subdistrict, Batu Bara Regency in 2021 - Mestika Rija Helti Tanjung (Institute of Computer Science (IOCS), 2021)
In the puerperium, there are usually wounds in the birth canal which are also called perineal wounds. Perineal wound healing if there is no infection will heal within 6-7 days. Based on the results of interviews, it was found that 7 out of 11 postpartum mothers had less knowledge about perineal care and wound healing took a long time. This research aimsJuan to find out the relationship between mother's knowledge about perineal wound care and Perineal wound healing belief in Limapuluh Village, Limapuluh Subdistrict in 2021. This research is an analytic survey with a cross sectional approach, data collection is carried out using a questionnaire, the research population is all postpartum mothers in the fifty sub-district fifty in July to September 2021, namely 47 mothers. The sampling technique in this study was carried out with a total sampling technique of the entire population as a sample. The results of the study found that from 47 respondents (100%) the majority of respondents' knowledge about perineal wound care was sufficient, namely 17 people (36.2%), fast wound healing as many as 29 people (61.7%). The results of the Chi-Square test (Pearson Chi-Square) at the 95% confidence level resulted in a P value of 0.000 (P <0.05) where H0 was rejected and Ha was accepted. This shows that there is a statistically significant relationship between mother's knowledge about perineal wound care and perineal wound healing in Lima Puluh Village, Fifty District in 2021. There is a relationship between mother's knowledge about perineal wound care and perineal wound healing in Limapuluh Subdistrict, Lima Puluh Tahun 2021. Therefore, it is recommended for mothers to increase knowledge about proper perineal wound care.